Basin and local scale detection of ground subsidence through persistent scatterer interferometry: The Anthemountas Basin (Northern Greece) case study. - Raspini, F.; Loupasakis, C.; Rozos, D.; Moretti, S. (Bulletin of the Geological Society of Greece, 2013)
In the framework of the Terrafirma Extension project, a study has been established for ground motion detection and mapping in the Anthemountas basin (Central Macedonia). Terrafirma promotes the exploitation of Persistent Scatterer Interferometry (PSI) techniques, a remote sensing technology based on multi-temporal satellite Synthetic Aperture Radar (SAR) imagery. The potential of SAR interferometry has been exploited through the innovative Wide Area Mapping approach, recently implemented by the German Space Agency (DLR) and aimed at measuring land deformation over large areas. Interferometric results from 1995-2001 by ERS1/2 satellites has been analyzed at a basin scale to investigate spatial patterns of land motion in the wider Anthemountas plain, where subsidence phenomena related to intense groundwater extraction is clearly manifested. The WAP results turned out to be a valuable tool for the characterization at local scale of the land subsidence in the runaways area of the Macedonia airport and in the village of Perea, affected in 2005-2006 by a series of tensile ground ruptures due to excessive groundwater withdrawal. Besides the study of the phenomenon, this work confirmed the suitability of PSI techniques to detect and measure surface displacements with millimetre accuracy and also to reconstruct the deformations history of the investigated areas through displacement time series analysis.